2009
DOI: 10.1167/iovs.08-2594
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Related Differences in Contrast Sensitivity in C57Bl/6 Mice

Abstract: OKR gains decrease as stimuli become more difficult to see, making the OKR a powerful tool to quantify contrast sensitivity. In C57BL/6 these response magnitudes vary greatly between sexes and between mice that differ only a few months in age. Therefore, it is important to match groups according to age and sex in experiments that require unimpaired vision. Otherwise, impaired vision can be misinterpreted as a learning or motor problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 32 publications
9
39
2
Order By: Relevance
“…Our estimates of contrast threshold of ϳ10% falls in the middle of a wide distribution of published thresholds for mice, which range from Ͻ1% (van Alphen et al, 2009) to 24% (Schmucker and Schaeffel, 2006). Studies relying on optomotor eye and head reflexes typically yield lower thresholds than the swimming task .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Our estimates of contrast threshold of ϳ10% falls in the middle of a wide distribution of published thresholds for mice, which range from Ͻ1% (van Alphen et al, 2009) to 24% (Schmucker and Schaeffel, 2006). Studies relying on optomotor eye and head reflexes typically yield lower thresholds than the swimming task .…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, different studies have used different definitions of threshold. Some studies define contrast threshold as the minimum contrast at which a response can be elicited (Prusky et al, 2000;Schmucker and Schaeffel, 2006;van Alphen et al, 2009). Others define it as the contrast that yields 70% correct responses Umino et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that melanopsin containing ganglion cells mediate this reflex even if no photoreceptors are left (Foster and Hankins, 2002). None of the mice tested was able to discriminate gratings from uniform fields (van Alphen et al, 2009). The only visual task successfully passed by both rd1/rd1 and ChR2rd1/rd1 mice was the discrimination of a bright field from a dark field.…”
Section: Discussionmentioning
confidence: 99%
“…All the behavioral analyses were performed blind with respect to the genotype of the mice. L7-PKCi mice and their control littermates were tested according to the SHIRPA protocol (Crawley, 1999) for comprehensive phenotype assessment prior to the experiment (De Zeeuw et al, 1998;Burguière et al, 2005;van Alphen et al, 2009). All experiments were performed in compliance with European Union Council animal ethics guidelines.…”
Section: Methodsmentioning
confidence: 99%